The Three Hundred project: galaxy groups do not survive cluster infall. Issue 1 (3rd October 2022) - Haggar, Roan; Kuchner, Ulrike; Gray, Meghan E; Pearce, Frazer R; Knebe, Alexander; Yepes, Gustavo; Cui, Weiguang
ABSTRACT: Galaxy clusters grow by accreting galaxies as individual objects, or as members of a galaxy group. These groups can strongly impact galaxy evolution, stripping the gas from galaxies, and enhancing the rate of galaxy mergers. However, it is not clear how the dynamics and structure of groups are affected when they interact with a large cluster, or whether all group members necessarily experience the same evolutionary processes. Using data from The Three Hundred project, a suite of 324 hydrodynamical resimulations of large galaxy clusters, we study the properties of 1340 groups passing through a cluster. We find that half of group galaxies become gravitationally unbound from the group by the first pericentre, typically just 0.5–1 Gyr after cluster entry. Most groups quickly mix with the cluster satellite population; only $8{{\ \rm per\ cent}}$ of infalling group haloes later leave the cluster, although for nearly half of these, all of their galaxies have become unbound, tidally disrupted or merged into the central by this stage. The position of galaxies in group-centric phase space is also important – only galaxies near the centre of a group ( r ≲ 0.7 R 200 ) remain bound once a group is inside a cluster, and slow-moving galaxies in the group centre are likely to be tidally disrupted, or merge with another galaxy. This work will help future observational studies to constrain the environmental histories of group galaxies. For example, groups observed inside or nearby to clusters have likely approached very recently, meaning that their galaxies will not have experienced a cluster environment before.